Coping Strategies of Students with Low Self-Control in Facing Assignment Deadlines - Aisya, Farah; Selian, Sri Nurhayati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
TThis study is based on the academic demands faced by university students, particularly in managing assignment deadlines that often lead to stress. The aim of this study was to explore the experiences of students with low self-control in facing assignment deadlines and the coping strategies they used. This study employed a descriptive qualitative method involving three students selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were analyzed using thematic analysis. The findings showed that students with low self-control tended to engage in academic procrastination, which led to increased deadline pressure, stress, anxiety, and psychological exhaustion. Coping strategies used by students included problem-focused and emotion-focused coping, which were influenced by task demands, emotional conditions, and self-regulation ability. In addition, social support and time management emerged as important contextual and regulatory factors that shape students’ ability to manage academic pressure. In conclusion, self-control, coping strategies, social support, and time management are interrelated factors that influence students' ability to manage assignment deadlines and psychological well-being.